Extracellular Inflammasome Particles Are Released After Marathon Running and Induce Proinflammatory Effects in Endothelial Cells - Kogel, Alexander; Fikenzer, Sven; Uhlmann, Luisa; Opitz, Lena; Kneuer, Jasmin M.; Haeusler, Karl Georg; Endres, Matthias; Kratzsch, Jürgen; Schwarz, Viktoria; Werner, Christian; Kalwa, Hermann; Gaul, Susanne; et al. (Frontiers in Physiology, 2022)
Objectives: The intracellular NLRP3 inflammasome is an important regulator of sterile inflammation. Recent data suggest that inflammasome particles can be released into circulation. The effects of exercise on circulating extracellular apoptosis-associated speck-like protein (ASC) particles and their effects on endothelial cells are not known. Methods: We established a flow cytometric method to quantitate extracellular ASC specks in human serum. ASC specks were quantitated in 52 marathon runners 24–72 h before, immediately after, and again 24–58 h after the run. For mechanistic characterization, NLRP3 inflammasome particles were isolated from a stable mutant NLRP3 (p.D303N)-YFP HEK cell line and used to treat primary human coronary artery endothelial cells. Results: Athletes showed a significant increase in serum concentration of circulating ASC specks immediately after the marathon (+52% compared with the baseline, p < 0.05) and a decrease during the follow-up after 24–58 h (12% reduction compared with immediately after the run, p < 0.01). Confocal microscopy revealed that human endothelial cells can internalize extracellular NLRP3 inflammasome particles. After internalization, endothelial cells showed an inflammatory response with a higher expression of the cell adhesion molecule ICAM1 (6.9-fold, p < 0.05) and increased adhesion of monocytes (1.5-fold, p < 0.05). Conclusion: These findings identify extracellular inflammasome particles as novel systemic mediators of cell–cell communication that are transiently increased after acute extensive exercise with a high mechanical muscular load.